Comments on "Free vibration of super elliptical plates with constant and variable thickness by Ritz method" - Bambill, Diana Virginia (2010)
Free vibration of super elliptical plates with constant and variable thickness by Ritz method has been reported. the shape of the plate in the x y plane can be defined by the super elliptical function. Calculating the area and perimeter of the region may give an idea about the convergence of the integration. the discussers also obtained the area sand perimeters using a finite element code, to be sure about the good precision of their values. The re-calculated values are in excellent agreement with Wang's results. The calculations have been performed for simply supported and clamped super elliptical plates with aspect ratio a/b=1, 1.2, 2, 3; with n=8 and n=10.